The Influence of Professionalism and Auditor Competency Towards Quality Audit Internal (Study on the Department of Housing, Residential Areas and Land Affairs Bandung Regency) - Noor, Julfan Herliansyah; Ainunnisa, Rarassatika; Arifin, Farid (Business Management, 2025)
This Jurnal entitled "The Influence of Auditor Professionalism and Competence on the Quality of Internal Audit Studies at the Department of Housing, Residential Areas and Land Affairs of Bandung Regency" This research is a quantitative study, which aims to determine: 1) the influence of auditor professionalism on internal audit quality, 2) the influence of auditor competence on internal audit quality, and 3) the influence of audit quality on internal audit quality. The sampling technique used was distributing questionnaires with a total of 30 respondents.Tests carried out in this study included validity tests, reliability tests, classic assumption tests (normality test, heteroscedasticity test and, multicollinearity test), simple linear regression, coefficient of determination test and t test which were processed using SPSS (Statistical Product and Service Solutions) software. ) for Windows version 19. The results of this study indicate that 1) there is an influence of auditor professionalism on internal audit quality. 2) there is an effect of auditor competence on internal audit quality. 3) there is an effect of audit quality on internal audit quality.